THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON ORGANIZATIONAL COMMITMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
Over the past few decades there has been tremendous growth in Emotional Intelligence research. It has been learned that since Emotional Intelligence is not a trait, appropriate intervention programmes can inculcate a combination of dynamic skills required for the same. Emotional Intelligence is an essential factor to be considered in an organizational setup. The present study attempts to determine the influence of Emotional Intelligence on Organizational Commitment and Organizational Citizenship Behavior. Commitment and Citizenship behavior are vital aspects of the organizational world. This study makes use of a sample of 115 Executives working at FCI OEN Connectors, Cochin, Kerala. The tools used for the study are Emotional Intelligence Inventory, The Organizational Commitment Questionnaire and The Organizational Citizenship Behavior Scale. The statistics used for the study are standard deviation and Pearsons product moment correlation. The results indicate that a positive relationship existed between Emotional Intelligence, Organizational Commitment and Organizational Citizenship Behavior.